2013
DOI: 10.3174/ajnr.a3779
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Cerebrospinal Venous Blood Flow and Vessel Anatomy with the Use of Phase Contrast-Vastly Undersampled Isotropic Projection Reconstruction and Contrast-Enhanced MRA

Abstract: BACKGROUND AND PURPOSE The chronic cerebrospinal venous insufficiency hypothesis raises interest in cerebrospinal venous blood flow imaging, which is more complex and less established than in arteries. For accurate assessment of venous flow in chronic cerebrospinal venous insufficiency diagnosis and research, we must account for physiologic changes in flow patterns. This study examines day-to-day flow variability in cerebrospinal veins by use of 4D MR flow and contrast-enhanced MRA under typical, uncontrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…4DFlow MRI has been shown to be accurate and reproducible for measuring dural sinus flow velocity, flow rate and demonstrating streamline flow in normal subjects [79]. In the sagittal sinus, blood flow velocity and blood flow rate increases from anterior to posterior as the sagittal sinus increases in size.…”
Section: Dflow Mri Dural Sinusesmentioning
confidence: 99%
See 2 more Smart Citations
“…4DFlow MRI has been shown to be accurate and reproducible for measuring dural sinus flow velocity, flow rate and demonstrating streamline flow in normal subjects [79]. In the sagittal sinus, blood flow velocity and blood flow rate increases from anterior to posterior as the sagittal sinus increases in size.…”
Section: Dflow Mri Dural Sinusesmentioning
confidence: 99%
“…Small venous structures are less reliably assessed due to limitations in spatial resolution and low signal due to very slow flow. Reference values for dural sinus velocity and blood flow rates in normal subjects are available for comparison across age groups and provide a foundation for developing clinical applications [79].…”
Section: Dflow Mri Dural Sinusesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of our findings, also confirmed by Chambers et al, 3 is that the flow increases as blood nears the heart. 2,4 On the other hand, in Table 1 of their article, Schrauben et al 1 reported that flow slightly decreases nearing the heart, by considering the left and right IJVs both as separated or as one. It is beyond the scope of this letter to compare the potential of the 2 modalities in assessing cerebrospinal flow.…”
mentioning
confidence: 99%
“…However, previous MR venography studies were hampered by their low specificity: Extracranial large veins may collapse with the patient in a supine position and consequently lead to stenosis or occlusions in MR angiography, which is physiologic and only temporary. 12,13 In the current issue of the American Journal of Neuroradiology, Schrauben et al 14 evaluate the accuracy and reproducibility of blood flow analysis by using MR imaging in both intra-and extracranial veins in 10 healthy volunteers. They used both contrast-enhanced MR angiography and 3D phase-contrast MR imaging with 3D velocity-encoding.…”
mentioning
confidence: 99%